A rhodium complex with one Rh...C-C and one Rh...H-C agostic bond. - Brayshaw, S; Green, J; Kociok-Köhn, G; Sceats, E; Weller, A (2006)
(Figure Presented) Hidden qualities: [Rh(PiPr3) (C 14H16)]-[BArF4] (1; see picture of the cation; P violet, Rh olive green), which was synthesized by treatment of [RhCl(nbd)-(PiPr3)] with Na[BArF4] (BAr F4 = B{C6H3-(CF3) 2}4) and norbornadiene (nbd) in fluorobenzene, contains an organic fragment derived from Binor-S as well as agostic Rh⋯CC and Rh⋯HC interactions. In solution, 1 undergoes rapid, reversible C-C activation/reductive elimination. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.